The cAMP/Protein Kinase A Pathway Regulates Virulence and Adaptation to Host Conditions in Cryptococcus neoformans - Caza, Mélissa; Kronstad, James W. (Frontiers in Cellular and Infection Microbiology, 2019)
Nutrient sensing is critical for adaptation of fungi to environmental and host conditions. The conserved cAMP/PKA signaling pathway contributes to adaptation by sensing the availability of key nutrients such as glucose and directing changes in gene expression and metabolism. Interestingly, the cAMP/PKA pathway in fungal pathogens also influences the expression of virulence determinants in response to nutritional and host signals. For instance, protein kinase A (PKA) in the human pathogen Cryptococcus neoformans plays a central role in orchestrating phenotypic changes, such as capsule elaboration and melanin production, that directly impact disease development. In this review, we focus first on insights into the role of the cAMP/PKA pathway in nutrient sensing for the model yeast Saccharomyces cerevisiae to provide a foundation for understanding the pathway in C. neoformans. We then discuss key features of cAMP/PKA signaling in C. neoformans including new insights emerging from the analysis of transcriptional and proteomic changes in strains with altered PKA activity and expression. Finally, we highlight recent studies that connect the cAMP/PKA pathway to cell surface remodeling and the formation of titan cells.